Carbazole Substituted BODIPYs - Gupta, Iti; Kesavan, Praseetha E. (Frontiers in Chemistry, 2019)
Difluoroboron-dipyrromethenes (BODIPYs) are highly popular fluorescent dyes with applications as NIR probes for bioimaging, fluorescent tags/sensors and as photosensitizers in cancer therapy and organic photovoltaics. This review concentrate on the synthesis and spectral properties of BODIPY dyes conjugated with carbazole heterocycle. The carbazole is an electron rich tricyclic compound and due to its excellent electronic properties, it is extensively used in the production of electroluminescent materials and polymers. This review highlights the recent progress made on the series of BODIPY derivatives containing carbazole ring at alpha, beta and meso-positions of the BODIPY skeleton. Carbazole based hybrid BODIPYs, carbazole linked aza-BODIPYs and carbazole-fused BODIPYs are also discussed.